1984
DOI: 10.1056/nejm198404053101402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Dioxide on Diaphragmatic Function in Human Beings

Abstract: We studied the effects of acute changes in the partial pressure of arterial carbon dioxide on diaphragmatic contractility and performance in four normal men. To study contractility we measured the ability of the diaphragm to generate pressure at a given level of excitation by determining the relation between the electrical activity of the diaphragm and transdiaphragmatic pressure during a voluntary quasi-isometric inspiratory effort carried out at different levels of end-tidal carbon dioxide. Our results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
4

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(56 citation statements)
references
References 26 publications
0
51
1
4
Order By: Relevance
“…Previous attempts to estimate the degree of motor-neuronal activation during breathing have used surface EMG of inspiratory muscles expressed relative to "maximal" values obtained during inhalation to TLC (12)(13)(14). We could have used a similar method to compare the neural drive in COPD patients and control sub- jects.…”
Section: Discussionmentioning
confidence: 98%
“…Previous attempts to estimate the degree of motor-neuronal activation during breathing have used surface EMG of inspiratory muscles expressed relative to "maximal" values obtained during inhalation to TLC (12)(13)(14). We could have used a similar method to compare the neural drive in COPD patients and control sub- jects.…”
Section: Discussionmentioning
confidence: 98%
“…Acute hypercapnia leads to intracellular acidosis that has marked effects upon muscle cell metabolism, including decreases in ATP, PCr and adenosine nucleotides [64,65]. Furthermore, acute hypercapnia in healthy humans reduces limb muscle and diaphragm contractility [66,67]. Findings from animal studies are conflicting; decreases in PCr and ATP/ADP ratios have been reported in rat muscles exposed to high carbon dioxide levels [68], whereas no differences were found in phosphate metabolite activity between hypercapnic and normocapnic rat diaphragms [69].…”
Section: Hypercapniamentioning
confidence: 94%
“…Hypercapnia impairs diaphragmatic contractility (41) (66). Muscle weakness renders the diaphragm more susceptible to fatigue because it increases the ratio (Pdi breath/Pdi max) by lowering the denominator, whereas the numerator is either unchanged or increased as in obstructive lung disease (39).…”
Section: The Diaphragm In Diseasementioning
confidence: 99%